Multivisceral abdominal transplantation - Soin, B; Friend, P (2002)
The availability of immunosuppressive regimens adequate to prevent rejection of the transplanted intestine has enabled the development of multivisceral transplantation. The technical, immunologic, and infective problems that remain are still prohibitive, and these complex procedures are performed in small numbers in a limited number of transplant centers. Further development is likely to require more specific immunosuppressive strategies and novel approaches to prevent the recurrence of malignancy after transplantation for extensive tumors. © 2002 Lippincott Williams and Wilkins, Inc.